Basic guidelines for preparing a case report - M. Papadopoulos (AOSIS, 2002)
Introduction: The case report approach is a method of publication frequently used by clinicians to share data. The case report is a valuable research and education resource. Purpose: The purpose of this article is to define a case report and to present basic guidelines for preparing a case report. Method: The case report should include an introduction, literature review, case description, outcome section, discussion and summary.  These components are presented and discussed briefly.